Increasing the production of Lab Lab, the ideal food for successful culture of the milkfish, Chanos chanos (Forsskal - Bensam, P (Indian Journal of Fisheries, 2011)
The favourite food item of the milkfish inthe South-East Asian countries, where it hasbeen cultured, is the benthic complex ofperiphyton called Lab Lab (Pillai 1962,Bardach et al. 1972). This is composed ofmicroscopic organisms, dominated chiefly byblue-green algae like Phormidium andOscillatoria, diatoms like Navicuta andPleurosigma, amphipods, nematodes, et